Cardiovascular risk profile of subjects with known diabetes from the middle- and high-income group population of Delhi: the DEDICOM survey - Nagpal, J.; Bhartia, A. (Diabetic medicine, 2008)
Aims  To determine the cardiovascular risk profile of known diabetic patients from the middle‐ and high‐income group populace of Delhi. Methods  A cross‐sectional survey was conducted using a probability proportionate to size (systematic) two‐stage cluster design. Thirty areas were selected for a house‐to‐house survey to recruit a minimum of 25 subjects (known diabetes ≥ 1 year; 35–65 years of age) per area. Data were collected by interview, blood sampling and from medical records. Scores from the Framingham, Joint British Society, United Kingdom Prospective Diabetes Study, Systematic Coronary Risk Evaluation, and Diabetes Epidemiology: Collaborative Analysis Of Diagnostic Criteria in Europe studies were used to calculate summary estimates of risk for coronary heart disease (CHD) and stroke. Results  Eight hundred and nineteen subjects (25–30 per cluster) were enrolled. The mean age of the subjects was 53.6 years, the mean duration since diagnosis was 8.1 years, the mean body mass index was 28.1 kg/m2, with 50.7% women; 74.3% had hypertension, 75.1% dyslipidaemia and 41.8% had poor glycaemic control (HbA1c > 8.0%); 8.4% had already had a myocardial infarction, whereas 2.3% had suffered a stroke. Only 17.6% were taking aspirin, 3.4% were on lipid‐lowering drugs and 11.6% were taking antihypertensive agents. The risk engines estimated a 10‐year CHD risk of 12.6–13.9% and a stroke risk of 5.1–5.7%. Conclusion  The study documents that the cardiovascular profile of known diabetes patients from the middle and higher income groups of Delhi is poor, strengthening the case for targeting interventions at patients, providers and other stakeholders for improvement.